2016
DOI: 10.5194/aab-59-235-2016
|View full text |Cite
|
Sign up to set email alerts
|

The effects of in ovo feeding of glutamine in broiler breeder eggs on hatchability, development of the gastrointestinal tract, growth performance and carcass characteristics of broiler chickens

Abstract: Abstract. The aim of the present study was to investigate the effect of in ovo feeding (IOF) of glutamine on hatchability, development of the gastrointestinal tract, growth performance and carcass characteristics of broiler chickens. Fertilized eggs were subjected to injections with glutamine (Gln) (10, 20, 30, 40 or 50 mg dissolved in 0.5 mL of dionized water) on day 7 of incubation. Hatchability, growth performance, carcass characteristics (carcass weight and relative weights of breast, thigh, heart, liver, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 28 publications
6
47
2
5
Order By: Relevance
“…Similarly, no significant effect of the in-ovo injection of broiler embryos with selected substances on feed conversion ratio were detected by Bhanja & Mandal (2005) and Salary et al (2014). In contrast, Salmanzadeh et al (2012) reported that the broilers submitted to in-ovo injection of glucose presented better feed conversion ratio during the rearing period than the control group. Feed intake and feed conversion ratio were not affected by supplemental propolis in broiler (Ziaran et al, 2005;Acikgoz et al, 2005;Canogullari et al, 2009;Mahmoud et al, 2013) and quail diets (Sahin et al, 2003).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Similarly, no significant effect of the in-ovo injection of broiler embryos with selected substances on feed conversion ratio were detected by Bhanja & Mandal (2005) and Salary et al (2014). In contrast, Salmanzadeh et al (2012) reported that the broilers submitted to in-ovo injection of glucose presented better feed conversion ratio during the rearing period than the control group. Feed intake and feed conversion ratio were not affected by supplemental propolis in broiler (Ziaran et al, 2005;Acikgoz et al, 2005;Canogullari et al, 2009;Mahmoud et al, 2013) and quail diets (Sahin et al, 2003).…”
Section: Discussionmentioning
confidence: 85%
“…Hatchability was increased by in-ovo injection with ascorbic acid (Ipek et al, 2004), L-arginine (Al-Daraji et al, 2012), and carbohydrates (Dong et al, 2013). However, hatchability was reduced by in-ovo injection with ascorbic acid (Sgavioli et al, 2015), organic trace minerals (Oliveira et al, 2015), glucose (Ebrahimnezhad et al, 2011), and glucose and magnesium (Salmanzadeh et al, 2012). In contrast, Bhanja & Mandal (2005), Nowaczewski et al (2012), Moore et al (1994), Shafey et al (2012), and Coskun et al (2014) reported that hatchability was not affected when eggs were injected with amino acids, vitamin C, hormones, carbohydrates, and pollen extract, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the post‐hatch performance, the use of carbohydrates improved weight gain in only one study (Salmanzadeh et al., ), and the final weight in three studies (Salmanzadeh, ; Salmanzadeh, Ebrahimnejad, Shahryar, Ashrafi, et al., ; Tako et al., ), when compared to the placebo group. Feed intake increased in only one (6%) study (Salmanzadeh, ) and feed conversion in three (17%) studies (Campos et al., ; Salmanzadeh, ; Salmanzadeh et al., ).…”
Section: Resultsmentioning
confidence: 99%